Rheological properties of synovial fluid due to viscosupplements: A review for osteoarthritis remedy. (November 2020) - More, S.; Kotiya, A.; Kotia, A.; Ghosh, S.K.; Spyrou, L.A.; Sarris, I.E.
Highlights: Synovial fluid concentration, molecular weight and rheological properties. Recent advancements of rheological properties of viscosupplementation. Commercial viscosupplements and the role of polymeric properties. Clinical studies on the effectiveness and challenges of viscosupplements. Abstract: The synovial fluid is a transparent electrolyte solution included in joints to provide lubrication helping the proper movement. It exhibits complex rheological properties due to the interaction among its constituents i.e. hyaluronic acid, albumin, lubricin and phospholipids. In degenerative osteoarthritis and inflammatory rheumatoid arthritis diseases, the quantity of synovial fluid and lubrication efficiency significantly deteriorates. In that case, viscosupplementation with intra-articular hyaluronic acid may be prescribed to replenish the concentration, the molecular weight and the rheological properties of natural synovial fluid. The present review concentrates on the recent advancements in viscosupplementation with emphasis into their rheological properties, its effects on the rheological behavior of synovial fluid, and finally its clinical effectiveness. Initially, the properties of synovial fluid are summarized, and then a discussion on commercial viscosupplements, the role of polymeric properties and their rheological properties are reviewed. Moreover, a detailed discussion on the clinical effectiveness and challenges of viscosupplements are provided.